Contribution of Parenting Self-Efficacy to Parent Involvement in Education in Nagari Koto Gaek - Darmi Febri Erika Putri; Rinaldi (Causalita, 2024)
When parents believe in their ability to perform parenting duties in a child, this is known as parenting self-efficacy. Parenting self-efficacy is one of the factors that affect parental involvement in education. This study aims to investigate the contribution of parenting self-efficacy working mother to parental involvement in education in Nagari Koto Gaek. This study is designed as a quantitative research with a type of correlational research. The sample in this study uses a purposive sampling technique and data is collected by distributing questionnaires directly. The participants in this study were 100 mothers who worked in Nagari Koto Gaek. The analysis used in this study is multiple linear regression analysis. The results of the study found that parenting self-efficacy contributed to parental involvement in education in Nagari Koto Gaek. Parenting elf-efficacy contributed to parental involvement in education for working mothers in Nagari Koto Gaek by 65.9%.